Killer whales of Antarctica: distribution and some aspects of biology - Yu. A. Mikhalev (Ukrainian Antarctic Journal, 2016)
The data mining orcas Odessa whaling fleet in the period 1961-1979 gg. Set the volume of production - 323 orcas. Dimensions 205 males ranged from 4.5 m to 9.0 m, their average length was 7.26 m. Dimensions 118 females ranged from 3.7 m to 7.7 m, with an average length of 6.42 m. Compiled monthly distribution maps whales in the Antarctic and neighboring waters. Traced their seasonal migrations. Most are groups of killer whales of between 5 to 15 individuals. Weighed gonads in 57 males and 63 females. The average length was equal to the testes of 55 cm and a diameter of 22 cm. The average weight of testis from adult males is 10 kg. Dimensions of females ovaries had an average of 10-12 cm long and 5-7 cm wide. The average ovary weight of about 200 g, about the same weight of a functioning corpus luteum of pregnancy. On the basis of the size of the sex glands and the number of tracks of corpora lutea of pregnancy on the ovaries of females, body proportions, and of the zone, the conclusion about the existence of in the Antarctic except ordinary orca (Orcinus orca Linnaeus, 1758) alsoformsa shorterbody - killer whales Orcinus nana.